Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Regards sur la société canadienne, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Insights on Canadian Society, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Validation culturelle d’un outil numérique francophone pour l’histoire médicale en soins de santé primaires - McGraw, Monica; Dionne Merlin, Marjolaine; Dion, Cynthia; Renaud, Julie; Légère, Danika; Poirier, Marie-Dominique (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
La technologie de santé numérique s’intègre dans les soins de santé améliorant l’engagement des patients dans les décisions partagées, favorisant ainsi leur prise en charge et la qualité des soins. FirstHx développe des outils innovants dans cette optique, mais leur mise en oeuvre est complexe pour la population francophone dans un contexte majoritairement anglophone. Cette étude vise à valider culturellement cet outil et à évaluer la satisfaction des utilisateurs. Une méthodologie mixte séquentielle explicative est employée en trois phases : un sondage quantitatif pour tester la clarté des questions, des entretiens semi-dirigés pour explorer la traduction culturelle et la convivialité, et une validation par des experts via la méthode Delphi. L’outil validé optimisera les pratiques cliniques, normalisera la saisie des données d’anamnèse et ouvrira de nouvelles perspectives de recherche. Cette validation offrira à la population francophone un accès équitable à des outils numériques innovants, renforçant leur engagement dans leurs soins. Digital health technology is being integrated into healthcare, improving patient engagement in shared decision-making, thereby promoting their care and the quality of care. FirstHx develops innovative tools with this goal in mind, but their implementation is complex for the Francophone population in a predominantly English-speaking context. This study aims to culturally validate this tool and assess user satisfaction. A sequential explanatory mixed-method approach is used in three phases: a quantitative survey to test question clarity, semi-structured interviews to explore cultural translation and user-friendliness, and validation by experts using the Delphi method. The validated tool will optimize clinical practices, standardize the collection of medical history data, and open new research opportunities. This validation will provide the Francophone population with equitable access to innovative digital tools, strengthening their engagement in their healthcare.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.